(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Banditry activities have exacerbated severe socio-economic consequences including maiming and sacking of people off their farm lands, homes and income-generation activities. The extent the menace has affected women’ income-generation activities in Katsina State was investigated using survey design approach. Multistage sampling technique was adopted to select 558 respondents. Data on respondents’ socio-economic characteristics, banditry forms, income-generation activities, causes and effect of banditry were collected using structured interview schedule. Frequency counts, percentages, mean, Chi-square, PPMC and ANOVA were employed in data analysis. Results indicate that majority had mean age of 37 years, household size of 9 people and less or equal #154877.20 annual income. Gun shooting, theft and burglary, cattle rustling and kidnapping were most frequent forms of banditry. Livestock farming/poultry, trading, food processing, and crop farming were major income-generation activities while connivance of bandits with locals, weak security architecture and extreme poverty were main causes. Level of effect across the state was high as gathering non-fish aquatic products, processing of fish, pot making, basket making, and crop farming activities were greatly reduced. PPMC result shows that household size significantly correlated with level of effect in the state (r = 0.093, p = 0.029) and in Batsari (r = 0.146, p = 0.047) LGA. Also, educational status (χ2 = 12.511, p = 0.006) showed significant association with level of effect. The test of difference using ANOVA showed that effect level was higher in Batsari (mean = 52.44) than in Safana (mean = 51.11) and Jibiya (mean = 51.11) LGAs.